Perceived partner support and post-traumatic symptoms after an acute cardiac event:A longitudinal study. (June 2023) - George-Levi, Sivan; Fait, Keren; Hod, Hanoch; Matezky, Shlomi; Vilchinsky, Noa
Objective: Cardiac disease induced post-traumatic stress symptoms (CDI-PTSS) have been associated with negative consequences for patients' mental and physical health. Identifying risk factors as well as potential buffers is necessary for understanding the development and maintenance of CDI-PTSS. The current study focused on the mediating and moderating role played by patients' perceptions of their partners' ways of providing support (active engagement, overprotection, and protective buffering) in the development and stabilization of CDI-PTSS levels over time. Method: Male patients ( N = 106) were recruited at hospitalization (T1 ) and completed the study's questionnaires at two time points: approximately four months after hospital discharge (T2 ) and approximately eight months after discharge (T3 ). Results: Structual equation modeling was used to test the study hypotheses. All three forms of T2 perceived partner support were positively associated with T2 CDI-PTSS levels which, in turn, were positively associated with T3 CDI-PTSS levels. The linear association between T2 and T3 CDI-PTSS was positive but decreased as perceived partner protective buffering levels increased. Conclusions: In the context of CDI-PTSS, perceived partner support seems to have a different effect than it has in non-traumatic illness contexts. Interventions for couples coping with CDI-PTSS should be designed accordingly.